Plant Cell Wall as a Key Player During Resistant and Susceptible Plant-Virus Interactions - Kozieł, Edmund; Otulak-Kozieł, Katarzyna; Bujarski, Józef Julian (Frontiers in Microbiology, 2021)
The cell wall is a complex and integral part of the plant cell. As a structural element it sustains the shape of the cell and mediates contact among internal and external factors. We have been aware of its involvement in both abiotic (like drought or frost) and biotic stresses (like bacteria or fungi) for some time. In contrast to bacterial and fungal pathogens, viruses are not mechanical destructors of host cell walls, but relatively little is known about remodeling of the plant cell wall in response to viral biotic stress. New research results indicate that the cell wall represents a crucial active component during the plant’s response to different viral infections. Apparently, cell wall genes and proteins play key roles during interaction, having a direct influence on the rebuilding of the cell wall architecture. The plant cell wall is involved in both susceptibility as well as resistance reactions. In this review we summarize important progress made in research on plant virus impact on cell wall remodeling. Analyses of essential defensive wall associated proteins in susceptible and resistant responses demonstrate that the components of cell wall metabolism can affect the spread of the virus as well as activate the apoplast- and symplast-based defense mechanisms, thus contributing to the complex network of the plant immune system. Although the cell wall reorganization during the plant-virus interaction remains a challenging task, the use of novel tools and methods to investigate its composition and structure will greatly contribute to our knowledge in the field.